Kedudukan Majelis Umum dalam Perserikatan Bangsa-Bangsa - Frederik Agnar Widjaja (Jurnal Hukum Lex Generalis, 2023)
The General Assembly is the main organ of the United Nations (UN). In this organ, all members, both large and small countries, all have equal voting rights. This organ functions as the main place of discussion and decision-making in every UN activity, which is carried out in the form of sessions that pass various resolutions. This study will discuss the regulations regarding membership, functions, and powers, and decision-making in the General Assembly that have been regulated in the UN Charter, as well as the application of these regulations in a case study related to the resolutions passed. Even though they do not have binding legal force, General Assembly resolutions can still have a significant effect on international relations.